Extracorporeal photopheresis as an immunomodulatory agent: Haematocrit‐dependent effects on natural killer cells. Issue 4 (31st July 2016) - Becherucci, V.; Allegro, E.; Brugnolo, F.; Piccini, L.; Gori, V.; Bisin, S.; Bindi, B.; Ceccantini, R.; Pavan, P.; Cunial, V.; Gentile, F.; Ermini, S.; et al.
Abstract: The GvHD is a major cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation (HSCT). Extracorporeal photopheresis (ECP) represents an alternative therapeutic strategy to immunosuppressive therapy. Although ECP is used since 1990s, the mechanism of action has not yet been completely clarified. We analyzed cells collected from 20 ECP procedures of 4 patients affected by chronic GvHD and, for comparison, Peripheral Blood Mononuclear Cells (PBMCs) of 10 healthy donors undergoing from same type of photochemiotherapy, evaluating by flow cytometry, the effects before and after photoactivation with 8‐MOP. The analysis showed a significant increase in cell death after ECP in particular in CD4 T lymphocytes as described in literature correlated with haematocrit value. Most interesting data emerge from the analysis of cytotoxic activity of NK cells, using flow cytometry analysis of surface expression of CD107a in the presence of target cells (K562). In all analyzed samples it was possible to document a statistically significant reduction of the cytotoxic activity of NK cells after photoactivation. The decrease of the cytotoxic activity was related to hematocrit value of leukoapheresis: in fact, lower HCT values were associated with a more marked reduction of cytotoxic activity. The study confirms literature data about the increase of cellular mortality induce by ECP. Furthermore, for the first time it is demonstrated that the ECP exerts a marked and significant inhibitory effect on the cytotoxic activity of NK cells. Our study suggests that lower values of hematocrit are associated with better treatment outcome.